2021
DOI: 10.1002/jclp.23245
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study investigating the efficacy of brief, phone‐based, behavioral interventions for burnout in graduate students

Abstract: Objective This pilot study tested the efficacy of two brief, phone‐administered, behavioral interventions derived from behavioral activation in reducing burnout among doctoral students. Methods Sixty‐six doctoral students demonstrating current high burnout were randomly assigned to one of three intervention conditions: (1) Reward: increasing pleasant, rewarding behaviors, (2) Approach: approaching important goals that they have been avoiding, or (3) Control: monitoring only. Results Results indicated that doct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…However, most of the tested interventions also tended to be longer than a single session and fewer than half (45%) of the studies included in the review compared their intervention to any kind of control group (let alone an active control), making outcomes incommensurate with one another. Some pilot studies of brief and remote burnout interventions have demonstrated acceptability, feasibility, and efficacy for graduate students (Fang et al, 2021;Wasil et al, 2021), however these interventions were not specifically designed for mental health clinician trainees who may experience additional responsibilities and challenges throughout the course of their graduate training. Overall, the mixed nature of present results and lack of power to detect small effects paint an inconclusive picture of this SSI's capacity to target overall burnout; this stands counter to the broader SSI literature, which supports the utility of SSIs for mental health challenges in treatment-seeking populations (Schleider & Weisz, 2017;Sung et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the tested interventions also tended to be longer than a single session and fewer than half (45%) of the studies included in the review compared their intervention to any kind of control group (let alone an active control), making outcomes incommensurate with one another. Some pilot studies of brief and remote burnout interventions have demonstrated acceptability, feasibility, and efficacy for graduate students (Fang et al, 2021;Wasil et al, 2021), however these interventions were not specifically designed for mental health clinician trainees who may experience additional responsibilities and challenges throughout the course of their graduate training. Overall, the mixed nature of present results and lack of power to detect small effects paint an inconclusive picture of this SSI's capacity to target overall burnout; this stands counter to the broader SSI literature, which supports the utility of SSIs for mental health challenges in treatment-seeking populations (Schleider & Weisz, 2017;Sung et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians experience burnout, in part, due to their significant workloads; as such, psychosocial interventions designed to support clinicians must seek to minimize placing additional burdens on them. Previous work has shown that brief, remotely delivered burnout interventions are feasible, acceptable, and preliminarily efficacious for graduate students (Fang et al, 2021;Wasil et al, 2021). Single-session interventions (SSIs), or focused, one-time encounters with clinicians or programs designed to target one clinical issue or motivate behavior change, are ideal prototypes for the design of brief and accessible burnout interventions .…”
Section: Psychologists' Burnoutmentioning
confidence: 99%
“…Total burnout was reduced compared to the control for an intervention designed to helps students approach important goals (that they had been avoiding; Fang et al, 2021) and for an intervention promoting skills for the transition from school, specifically in individuals with learning difficulties (Vuori et al, 2008). Effect sizes were medium-sized (g = 0.65).…”
Section: Rational Emotive Behavior Therapymentioning
confidence: 92%
“…Psychoeducation Four studies adopted interventions that could be considered psychoeducational (systematic and structured knowledge transfer) (two randomized controlled trials and two quasi-experimental studies; Charbonnier et al, 2022;Fang et al, 2021;Noh et al, 2020;Vuori et al, 2008). They were all delivered in a range of formats (online, phone, in person) and ranged from 1 to 8 weeks in duration.…”
Section: Rational Emotive Behavior Therapymentioning
confidence: 99%